Pelaksanaan Lelang Eksekusi Atas Hak Tanggungan Akibat Kredit Macet Pada Bank - Melay, Adrin Stevani; Laturette, Adonia Ivonne; Haliwela, Nancy Silvana (PATTIMURA Law Study Review, 2025)
The implementation of the execution auction of mortgage rights due to bad debts at the bank which is carried out in accordance with Article 6 Number 4 of Law 1996 concerning Mortgage Rights involves complex legal procedures in the context of credit agreements. In this context, the credit given to CV. Dumai Putra Riau experienced problems due to bad debts, which led to the collateral auction process. The auction process carried out on March 19, 2015 showed that the collateral sale value was insufficient to cover all of the debtor's debts, leaving a remaining debt of IDR. 29,000,000.00. This happened because of the poor physical condition of the collateral, including damage to the building and a non-strategic location. From a legal perspective, this case reflects the responsibility that arises due to negligence, as regulated in Article 1366 of the Civil Code. The type of legal research used is normative juridical, which is carried out by examining legal principles and concepts, as well as laws and regulations. The legal research method used refers to primary, secondary, tertiary legal materials, with a statutory approach and a conceptual approach as well as the collection and analysis of legal materials. The purpose of this research is to find out the implementation of the auction of the execution of mortgage rights and the debtor's responsibility due to bad credit at the bank. The results of the study indicate that transparent law enforcement and a deep understanding of rights and obligations are the keys to avoiding legal disputes in the banking world and debtors remain legally obliged to settle the remaining debts that have not been covered by the auction results. In line with responsibility based on errors, even though the collateral has been auctioned, the debtor remains legally obliged to settle the remaining debts that have not been covered by the auction results. Related to the results of the execution of mortgage rights that are not sufficient in paying off debts, the bank or creditor can execute other assets belonging to the debtor. This is of course related to Article 1131 of the Civil Code, but in executing other assets outside the collateral in terms of debt repayment, a lawsuit should be filed first in terms of fulfilling the repayment of the remaining receivables that have not been paid in court.